Real‐World Prevalence, Treatment Patterns, and Outcomes for Patients With HER2 (ERBB2)‐Mutant Metastatic Non‐Small Cell Lung Cancer, From a US‐Based Clinico‐Genomic Database - Sarah Waliany; Misako Nagasaka; Leah Park; Clara Lam; Zoe Jiang; Feng Lin; Joel W. Neal (Cancer Medicine)
ABSTRACT Objectives Targeted therapies have been shown to improve outcomes in metastatic non‐small cell lung cancer (mNSCLC) with driver mutations. We evaluated the real‐world prevalence of human epidermal growth factor receptor 2 (HER2; ERBB2) tumor gene mutations among patients with mNSCLC and described historical treatments and outcomes in patients with HER2‐mutant mNSCLC, during a period when there was no approved targeted therapy for HER2‐mutant mNSCLC. Materials and Methods This retrospective observational study used a US nationwide de‐identified NSCLC clinico‐genomic database. Eligible patients were adults diagnosed with HER2‐mutant mNSCLC from January 2014 to July 2021 without co‐occuring epidermal growth factor receptor (EGFR) tumor mutations. Descriptive statistics were used to summarize prevalence, baseline characteristics and treatment patterns. Clinical outcomes were estimated with Kaplan–Meier analyses. Results Among 9206 patients with mNSCLC, 164 (1.78%) met the eligibility criteria (mean age: 67.3 years, 63.4% White, 56.7% female, and 53.0% with a smoking history). 132/164 (80.5%) had at least one line of treatment. Platinum‐based chemotherapy (45.5%) and immune checkpoint inhibitor (ICI) with chemotherapy (28.0%) were the most frequently used first‐line treatments. The median (95% confidence interval [CI]) real‐world (rw) progression‐free survival in first‐line was 5.5 (4.8, 6.2) months and 3.0 (2.3, 4.2) months in second‐line. The median rw overall survival in first‐line was 13.2 (10.6, 18.4) months and 8.2 (6.6, 13.2) months in second‐line. Conclusion During this study period, the most common regimens were platinum‐based chemotherapy with or without ICI in first and second line, and median rwOS was 13.2 and 8.2 months, respectively. These results indicate the need for more effective targeted therapies in this patient population.